Defining the Role of Service Design in Healthcare. (9th October 2013) - Teso, Giulia; Ceppi, Giulio; Furlanetto, Annarita; Dario, Claudio; Scannapieco, Gianluigi
<x xml:space="preserve">Abstract</x> Developments in information technology, as well as the need to conserve resources, are resulting in healthcare systems that place increased value on the patient's input. In Italy, the national health service has taken notice. The national healthcare service: It's hard to think of a system in which good service design could be more important.